Faktor-Faktor Yang Mempengaruhi Dividend Payout Ratio Pada Perusahaan Manufaktur Di Bei Tahun 2012-2014`` - NURJAYANTI, NOVITA PUTRI (2016)
This study aims at testing the effect of profitability, free cash flow, likuidity, and debt policy on the dividend payout ratio of manufacturing companies, listed on the Indonesia Stock Exchange. The study collected empirical data from the Indonesia Stock Exchange consisting of 32 companies. The data were collected from financial report from three consecutive years (2012-2014). Multiple regression was employed to analyze data. The results of the analysis variable profitability and free cash flow significant effect on dividend payout ratio, meanwhile the likuidity and debt policy do not effect on the dividend payout ratio.